NOP2/Sun RNA Methyltransferase 4 Regulates the Mammalian Target of Rapamycin Signaling Pathway to Promote Hepatocellular Carcinoma Progression - Congren Wang; Shaoying Ke; Shaoze Lin; Conglin Lin; Zhibing Cai; Lingju Hong; Qunxiong Pan (The Turkish Journal of Gastroenterology)
Background/Aims: NOP2/Sun RNA methyltransferase 4 (NSUN4) is a prognostic indicator for hepatocellular carcinoma (HCC). However, the mechanism of NSUN4 in HCC is still unexplored. This project mainly focuses on the function and mechanism of NSUN4 in HCC malignant progression.